2014
DOI: 10.1507/endocrj.ej14-0004
|View full text |Cite
|
Sign up to set email alerts
|

High serum parathyroid hormone and calcium are risk factors for hypertension in Japanese patients

Abstract: Parathyroid hormone (PTH) plays an important role in bone resorption and renal calcium reabsorption. Excess PTH, known as primary hyperparathyroidism (pHPT), results in hypercalcemia and bone loss [1] and is reported to be associated with high cardiovascular morbidity and mortality in both hypercalcemia-dependent and -independent manners [2][3][4][5]. Several studies have suggested that PTH levels are associated with hypertension and hypertension-related organ damage, including left ventricular hypertrophy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
0
12
1
Order By: Relevance
“…A PubMed search using the key words ‘normocalcaemic hyperparathyroidism’ returned 453 articles, of which 54 were original clinical NCHP studies. BP was reported in five studies including 553 individuals (70 patients with NCHP and 662 controls). Systolic BP was 3·6% (95% CI: −0·4 to 7·6%), and diastolic BP was 2·9% (95% CI: −1·7 to 9·3%) higher in patients with NCHP compared to controls (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A PubMed search using the key words ‘normocalcaemic hyperparathyroidism’ returned 453 articles, of which 54 were original clinical NCHP studies. BP was reported in five studies including 553 individuals (70 patients with NCHP and 662 controls). Systolic BP was 3·6% (95% CI: −0·4 to 7·6%), and diastolic BP was 2·9% (95% CI: −1·7 to 9·3%) higher in patients with NCHP compared to controls (Fig.…”
mentioning
confidence: 99%
“…Comparison of systolic ( SBP ) and diastolic blood pressure ( DBP ) in published studies between patients with normocalcaemic hyperparathyroidism and age‐ and gender‐matched controls.…”
mentioning
confidence: 99%
“…PTH regulates calcium, phosphorus and magnesium levels in the bones and blood through the kidneys , bones and intestines. An increase in serum PTH levels leaves patients prone to develop incident HT [ 3 5 ]. The association between PTH and BP in HT patients has been studied by many researchers, nevertheless the results of their studies are conflicting [ 8 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have stated that lower levels of vitamin D are associated with incident HT [ 1 , 2 ]. Moreover, other studies have shown that elevated serum PTH levels are related with an increased risk of HT development [ 3 , 4 ] even in patients with normal serum PTH levels [ 5 ]. It is well known that primary hyperparathyroidism is associated with established HT and that parathyroidectomy significantly reduces blood pressure (BP) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study from the United States with 191 obese participants (BMI 43 -9.2 kg/m2), there was no correlation between 25(OH)D levels and TC, TG, HDL-C, or LDL-C. 37 Recent studies have shown that hyperparathyroidism is correlated with arteriosclerosis and hypertension. [38][39][40] It has been shown that PTH levels within the upper normal range were related to cardiovascular disease in the elderly. 8 There appeared to be an activation of the renin-angiotensinaldosterone system in hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%